High-entropy alloying modified copper-tin alloy and preparation method and application thereof
Through high-entropy alloying modification technology and pseudo-binary reaction preparation technology, the lack of performance of traditional copper-tin oil-containing bearings in high load, high wear and high temperature environments is solved, and higher load-bearing capacity, wear resistance and high temperature stability are achieved, extending service life and reducing costs.
Patent Information
- Application Number
- CN202510049642.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional copper-tin oil-containing bearings show problems such as insufficient load capacity, poor wear resistance and high cost under high load, high wear and high temperature environments.
High-entropy alloying modification technology is adopted, and by mixing copper-tin alloy powder with high melting point and low melting point components and using pseudobinary reaction preparation technology, the diffusion and interaction between elements are optimized to form complex microstructures and optimized lattice characteristics, thereby improving the hardness, wear resistance and high temperature stability of the material.
It significantly improves the bearing capacity, wear resistance and high temperature stability of copper-tin alloy bearings, extends the service life of the bearings, and reduces material costs.
Smart Images

Figure CN119870468A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy materials, and in particular relates to a high-entropy alloyed modified copper-tin alloy and a preparation method and application thereof. Background Art
[0002] In the field of mechanical manufacturing and industrial applications, bearings are key support and transmission components, and their performance directly affects the stability, operating efficiency and service life of mechanical equipment. Traditional copper-tin oil-containing bearings have been widely used in low-speed and light-load applications due to their excellent self-lubricating properties. These bearings are prepared by powder metallurgy technology, have a low friction coefficient and good self-lubricating ability, and can operate stably for a long time without external lubrication. However, with the development of industrial technology and the continuous improvement of bearing performance requirements, the performance of traditional copper-tin oil-containing bearings has gradually failed to meet application requirements. First, the load-bearing capacity of traditional copper-tin oil-containing bearings is weak, and it is difficult to meet the needs of high-load conditions. In addition, insufficient wear resistance is also an important factor limiting its application range. In a high-wear environment, the service life of copper-tin oil-containing bearings will be greatly shortened. Furthermore, due to the high tin content of traditional copper-tin oil-containing bearings, the material cost is high, which is not conducive to large-scale application.
[0003] High entropy alloys have unique microstructures and excellent physical properties, such as high hardness, excellent wear resistance, fatigue resistance, high temperature stability and corrosion resistance. Their material design concept can be used to improve the service performance of copper-tin oil-bearing bearings. High entropy alloys are usually composed of five or more elements in a nearly equiatomic ratio. This design breaks the boundaries between major and minor elements in traditional alloys, allowing the alloys to exhibit unprecedented performance. Their strengthening mechanisms, such as diffusion retardation effect, lattice distortion and "cocktail" effect, jointly improve the overall performance of the material. Lattice distortion is caused by differences in element size, bond type and lattice energy, which increases hardness and strength; while the diffusion retardation effect enhances wear resistance and fatigue resistance by reducing the atomic diffusion rate; the "cocktail" effect uses the combined effects of each main element to improve macroscopic performance and achieve additional functional benefits.
[0004] Applying high entropy alloying technology to the modification of copper-tin oil-containing bearings is expected to achieve the following technical effects: improved load-bearing capacity, enhanced wear resistance, reduced costs, improved high-temperature stability, and enhanced corrosion resistance. These improvements will enable bearings to perform well in a wider range of applications, especially under high loads, high wear, high temperatures, and harsh environments. In addition, high entropy alloying modification may also bring additional performance improvements, such as improving the thermal expansion properties of bearings and reducing performance fluctuations caused by temperature changes.
[0005] Although high entropy alloying modification has obvious advantages, it still faces some technical challenges in practical applications. For example, the preparation process of high entropy alloys is relatively complex and the cost is high. As an innovative approach, pseudo-binary reaction technology has significant advantages in the preparation of alloy porous materials. This technology combines elements with different melting points to optimize the diffusion and interaction between elements, thereby improving the microstructure and comprehensive properties of the material. Combined with the high entropy alloy system, pseudo-binary modification can significantly improve the material's load-bearing capacity, wear resistance, and chemical and thermal stability. Therefore, the development of an economical, efficient and reliable high entropy alloying modification method is of great significance for improving the performance of copper-tin oil-containing bearings. Summary of the invention
[0006] In order to solve the problem that the service performance of existing copper-tin alloy bearings is insufficient, and although high entropy alloying treatment has the possibility of improving the performance of copper-tin alloy materials in theory, an effective method for high entropy treatment thereof has not yet been developed, the present invention provides a high entropy alloyed modified copper-tin alloy, as well as a preparation method and application of the copper-tin alloy.
[0007] The main purpose of the present invention is: 1. Effectively realize high-entropy alloying of copper-tin alloys, and improve the hardness and strength of the material through the complex microstructure and optimized lattice characteristics of high-entropy alloys, thereby enhancing its load-bearing capacity under high load conditions; Second, the diffusion retardation effect and lattice distortion in high entropy alloys are used to improve the wear resistance of the material, so that the bearing can maintain a longer service life in a high wear environment; 3. Through the high temperature stability of high entropy alloys, the performance stability of bearings in environments with large temperature fluctuations is improved, and the performance fluctuations caused by temperature are reduced; 4. The "cocktail" effect of high entropy alloys improves the chemical stability of the material, thereby enhancing its durability in corrosive environments; 5. By adopting pseudo-binary reaction preparation technology, the preparation process is optimized, the burning of expensive materials is reduced, and the production efficiency is improved, thereby reducing the overall cost.
[0008] To achieve the above objectives, the present invention adopts the following technical solutions.
[0009] A high entropy alloying modified copper-tin alloy, The method comprises: 1) respectively taking copper alloy powder and tin alloy powder and mixing them evenly to obtain mixed powder; 2) The mixed powder is granulated and pressed to obtain a green body, and the green body is sintered in multiple stages to obtain a high entropy alloyed modified copper-tin alloy.
[0010] As a preference, Step 1) the copper-containing alloy powder is composed of copper element and high melting point components; The melting point of the high melting point component is ≥1000°C; Step 1) the tin-containing alloy powder is composed of tin element and low melting point components; The melting point of the low melting point component is less than 1000°C.
[0011] As a preference, Step 1) The copper-containing alloy powder is CuMnNi alloy powder, and its component percentage is: Cu 60~65 wt%, Mn 10~30%, the balance is Ni; Step 1) The tin-containing alloy powder is SnZnPb alloy powder, and its component percentage is: Sn 50~60 wt%, Zn 35~45 wt%, and the balance is Pb.
[0012] As a preference, Step 1) The mass proportion of the copper alloy powder in the mixed powder is 80-95%, and the remainder is tin alloy powder.
[0013] As a preference, Step 1) The mixing is carried out by the following method: The copper-containing alloy powder and the tin-containing alloy powder are placed in a mixing bottle filled with protective gas, put into a mixer for mixing, and zirconium oxide balls are added as a mixing medium during the mixing process, and mixed for 24 to 48 hours.
[0014] As a preference, Step 2) The granulation process is: Add the mixed powder to the ethanol solution containing the binder, mix and stir until it is dry, then crush and sieve to control the powder particle size to 100-300 mesh; The mass ratio of the binder to ethanol in the binder-containing ethanol solution is 1:(0.95-1.05), the amount of the binder is 2-3 wt% of the mixed powder, and the binder used is a binder soluble in ethanol.
[0015] As a preference, Step 2) the pressing process controls the pressing pressure to be 50-250 MPa; Step 2) the multi-stage sintering is carried out under reducing gas and / or inert gas, or vacuum protection conditions; When the multi-stage sintering is carried out under vacuum protection, the vacuum degree is controlled to be 1.0×10 -2 ~1×10 0 Pa; Step 2) The multi-stage sintering includes low-temperature sintering and high-temperature sintering.
[0016] As a preference, The low temperature sintering is a gradient heat treatment in the range of 120-420°C, which includes preheating at 120-150°C for 5-15 min, initial sintering at 180-220°C for 90-150 min, and debonding at 380-420°C for 25-35 min. The high temperature sintering is carried out at a temperature of ≥800°C and less than the melting point of the components contained in the copper alloy powder, and the sintering time is 1 to 3 hours.
[0017] The high temperature sintering is carried out at a temperature of ≥800°C and less than the melting point of the components contained in the copper alloy powder, and the sintering time is 1 to 3 hours.
[0018] A high entropy alloying modified copper-tin alloy.
[0019] Application of a high entropy alloying modified copper-tin alloy, The high entropy alloyed modified copper-tin alloy is used for manufacturing oil-containing bearings.
[0020] For the technical solution of the present invention, the most important and core process is to use high entropy alloying and pseudo-binary reaction on the copper-tin alloy to obtain CuMnNi-10 (SnZnPb) porous high entropy alloy to replace the traditional Cu10Sn porous alloy material.
[0021] Conventional high entropy alloy preparation technology generally involves mixing and smelting various alloy elements, and then preparing powders through atomization. Due to the large difference in the melting points of high-melting point and low-melting point elements in the copper-tin-based alloy system, the volatilization and burning of low-melting point elements during the smelting process are more serious. Moreover, the alloy powder obtained after atomization of high entropy alloys with more than 5 constituent elements has high yield strength, poor formability and poor sintering activity, so it is difficult to use it directly in the manufacture of oil-containing bearings.
[0022] However, in the technical solution of the present invention, due to the adoption of the idea of high entropy alloying and pseudo-binary reaction, the melting point difference between high melting point and low melting point components is comprehensively considered, a "pseudo-binary" reaction system is constructed by grouping limited alloying, and further a fully alloyed high entropy alloy porous material is prepared by partial diffusion and alloying of the two components. Among them, the copper element has a high solid solubility with elements such as nickel, aluminum, zinc, manganese and tin. Therefore, in the alloy design, copper, manganese and nickel are selected as high melting point components to form the main skeleton part of the porous alloy. The tin element has a certain solid solubility with elements such as zinc, lead and bismuth, so tin, lead and zinc are used as low melting point components. Through reasonable pre-alloying and selection of alloy powder, the powder forming performance is significantly improved compared with high entropy alloy powder; the elements in the two pre-alloy components interact with each other during high temperature sintering, and promote the pore formation and organization optimization of the porous alloy material. Especially under the partial diffusion effect between high melting point elements (such as copper, manganese, nickel) and low melting point elements (such as tin, lead, zinc), the sintering activity of the alloy is improved, the sintering temperature is significantly reduced, and the problem of component segregation during the sintering process is effectively suppressed, thereby improving the mechanical properties, hardness, wear resistance and high temperature stability of the alloy.
[0023] In addition, for the technical solution of the present invention, the final calcination process is also carried out in the form of segmented sintering. Due to the composition characteristics of the high entropy alloy of the present invention, after pressing the green body, it is first necessary to degrease by low-temperature sintering, and then sinter at high temperature by gradient heating. Since the low-melting point components have been alloyed, the sintering process does not need to be kept warm at the melting point of each element, and the sintering process is simplified. The overall sintering process should be carried out in a quasi-solid phase or transient liquid phase state to avoid excessive liquid phase generation and retention, resulting in a decrease in the pore structure, dimensional accuracy, composition uniformity and performance controllability of the product, which is beneficial to improving the strength and toughness of the material.
[0024] 1) The present invention significantly improves the crushing strength and hardness of copper-tin oil-containing bearings by adopting a high entropy alloying method. The complex microstructure and lattice property optimization of the high entropy alloy significantly improve the load-bearing capacity of copper-tin-based oil-containing bearings under high load conditions, thereby meeting more stringent industrial application requirements.
[0025] 2) The present invention adopts a pseudo-binary reaction method to improve the process performance of porous high-entropy alloys by pre-alloying high-melting point elements (such as Cu, Mn, Ni) and low-melting point elements (such as Sn, Pb, Zn) and then diffusion sintering. This method not only ensures the formability and composition uniformity of the powder, but also reduces the difficulty of sintering, so that the porous alloy material finally prepared has excellent mechanical properties, corrosion resistance and high-temperature stability, and effectively improves the service life of the material.
[0026] 3) The CuMnNi-10 (SnZnPb) alloy of the present invention significantly improves the mechanical properties and wear resistance of oil-containing bearings through the high entropy effect, allowing the bearings to work stably at higher temperatures and greater loads. The application of pseudo-binary reaction technology further optimizes the microstructure of the alloy, enhances the uniformity and stability of the material, and significantly extends the service life of the bearings. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a surface SEM image of the CuMnNi-10 (SnZnPb) porous high entropy alloy material prepared in Example 1 of the present invention; Figure 2 is a cross-sectional element distribution diagram of the CuMnNi-10 (SnZnPb) porous high entropy alloy material prepared in Example 1 of the present invention; Figure 3 It is a cross-sectional element distribution diagram of the CuMnNi-10 (SnZnPb) porous high entropy alloy material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in conjunction with specific embodiments and the accompanying drawings. A person of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by a person of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0029] In the description of the present invention, it should be understood that the terms "thickness", "upper", "lower", "horizontal", "top", "bottom", "inner", "outer", "circumferential" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In the description of the present invention, "multiple" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined, and "several" means one or more.
[0030] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral one; it can be a mechanical connection, an electrical connection, or communication with each other; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0031] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0032] Example 1 A method for preparing a high entropy alloyed modified copper-tin alloy, which specifically comprises: (1) Powder preparation: CuMnNi alloy powder (purity>99.5 wt%, Cu 60 wt%, Mn30 wt%, Ni 10 wt%) with a particle size of 40-55 μm and SnZnPb alloy powder (particle size of about 60 μm, purity>99.5 wt%, Sn 60 wt%, Zn 38wt%, Pb 2 wt%) were taken, and 90% of the CuMnNi alloy powder and 10% of the SnZnPb alloy powder were mixed evenly according to the mass percentage. The powders were mixed into a mixed powder in a nitrogen-protected V-type mixer. In order to obtain a uniform mixture, zirconium oxide balls were added to the original powder to improve the mixing efficiency. Each batch of powder was blended for 24 hours. (2) Granulation: Then, ethanol is used as a solvent and stearic acid accounting for 2.0 wt.% of the total mass of the mixed powder is mixed in a volume ratio of 1:1, and then the mixed powder is added to mix and granulation is performed to improve the compression molding effect of the sample; (3) Pressing: The granulated powder is dried and crushed again with a 100-mesh sieve, placed in a molding die, and pressed into a sheet (φ10 mm×2.0 mm) at a pressure of 200 MPa; (4) Sintering: When the vacuum degree is less than 1.0×10 -2Pa vacuum sintering furnace, the green body reaction synthesis was carried out by step sintering method, from room temperature to 150 ℃, the heating rate was 10 ℃ / min, and the temperature was kept at this temperature for 10 min to remove the gas molecules adsorbed by the green body, and then the temperature was continued to rise to 200 ℃, the heating rate was 2 ℃ / min, and the temperature was kept at this temperature for 2 h. At this stage, the Kirkendall effect began to play a role, which helped to promote the diffusion and mixing between different elements. This process helped to form a good structure of the alloy and promote the formation of pores. Then the temperature was continued to rise to 400 ℃, the heating rate was 5 ℃ / min, and the temperature was kept at this temperature for 30 min to remove the binder in the green body, and the temperature was continued to rise to 900 ℃, the heating rate was 5 ℃ / min, and the temperature was kept for 2 h to promote the diffusion between the elements and the growth of the sintering neck to obtain a porous alloy material with uniform composition, good sintering neck and interconnected pore structure, that is, high entropy alloying modified copper-tin alloy.
[0033] The prepared porous alloy material was characterized by SEM and mapping element distribution. The characterization results are as follows: Figure 1 and Figure 2 As shown. From the characterization results, it can be clearly seen that a stable porous structure was effectively constructed and formed during the preparation process, and a multi-layer sintering neck and pore structure were formed. On the basis of the pore structure, a multi-layer three-dimensional structure was further formed. In the element characterization result diagram, Cu, Mn, Ni, Sn, Pb and Zn all showed extremely high distribution uniformity, and basically no segregation occurred.
[0034] The mechanical properties of the sintered product in this example were characterized, and the characterization results are shown in the following table. Hardness (HV) Crushing strength Porosity 231 372 MPa 23.2%
[0035] The corresponding mechanical properties data of commercially available high-quality Cu10Sn alloy are as follows. Hardness (HV) Crushing strength Porosity 152 233 MPa 20.2%
[0036] From the above characterization results, it can be seen that the copper-tin alloy prepared by the technical solution of the present invention shows far superior performance to conventional Cu10Sn alloy in terms of mechanical properties characterization results such as hardness and crushing strength. Among them, because the addition of multiple elements will disrupt the lattice structure of the alloy, increase the lattice distortion and dislocation density, thereby hindering the movement of dislocations and improving the hardness of the alloy, in addition, the solid solution strengthening of multiple principal elements and the second phase formed will further enhance the hardness. Similarly, the addition of multiple elements will also lead to a significant improvement in the tensile strength and yield strength of the alloy through solid solution strengthening, grain boundary strengthening and precipitation strengthening.
[0037] Comparative Example 1 A method for preparing a high entropy alloyed modified copper-tin alloy is based on the preparation process of Example 1, except that: The CuMnNi alloy powder and the SnZnPb alloy powder are replaced with Cu powder, Mn powder, Ni powder, Sn powder, Pb powder and Zn powder in corresponding proportions, respectively.
[0038] Based on the porous alloy material prepared by the above method (i.e., high entropy alloying modified copper-tin alloy), the prepared porous alloy material is subjected to mapping characterization. The characterization results are as follows: Figure 3 As shown. Figure 3 From the characterization results, it can be seen that the Sn element has obvious segregation and enrichment. This is because during the high-temperature sintering process, the diffusion rate of low-melting-point elements is faster and they are easily enriched in certain areas of the sintered body, especially in the early stages of the sintering process, which may form local Sn-rich areas. In addition, in the alloy, the solid solubility between Sn and Pb and Zn is limited. Especially at high temperatures, the mutual solubility of these three elements is low, which makes them easily form segregation areas in the alloy.
[0039] The alloy product of this example was made into a standard sample for mechanical property characterization, and the characterization results are shown in the following table. Hardness (HV) Crushing strength Porosity 196 302 MPa 23.3%
[0040] From the above characterization results, simply mixing the elements to form an alloy of the same composition cannot play a good synergistic role to construct a high-entropy alloy with a specific high-quality structure. Its hardness, tensile strength and yield strength are not as good as the sample prepared in Example 1, and the elongation at break has further decreased. This indicates that it may have serious segregation, or element burning, volatilization, etc., resulting in a significant increase in its brittleness and failure to produce good synergistic strengthening.
[0041] Example 2 A method for preparing a high entropy alloyed modified copper-tin alloy, which specifically comprises: (1) Powder preparation: CuMnNi alloy powder (purity>99.5 wt%, Cu 60 wt%, Mn10 wt%, Ni 30 wt%) with a particle size of 40-55 μm and SnZnPb alloy powder (particle size of about 60 μm, purity>99.5 wt%, Sn 50 wt%, Zn 45wt%, Pb 5 wt%) were taken, and 90% of the CuMnNi alloy powder and 10% of the SnZnPb alloy powder were mixed evenly according to the mass percentage. The powders were mixed into a mixed powder in a nitrogen-protected V-type mixer. In order to obtain a uniform mixture, zirconium oxide balls were added to the original powder to improve the mixing efficiency. Each batch of powder was blended for 24 hours. (2) Granulation: Then, ethanol is used as a solvent and stearic acid accounting for 2.0 wt.% of the total mass of the mixed powder is mixed in a volume ratio of 1:1, and then the mixed powder is added to mix and granulation is performed to improve the compression molding effect of the sample; (3) Pressing: The mixed powder after granulation is dried and crushed again through a 100-mesh sieve, placed in a molding die, and pressed into a sheet (φ10 mm×2.0 mm) at a pressure of 200 MPa; (4) Sintering: When the vacuum degree is less than 1.0×10 -2 Pa vacuum sintering furnace, the green body reaction synthesis was carried out by step sintering method, from room temperature to 150 ℃, the heating rate was 10 ℃ / min, and the temperature was kept at this temperature for 10 min to remove the gas molecules adsorbed by the green body, and then the temperature was continued to rise to 200 ℃, the heating rate was 2 ℃ / min, and the temperature was kept at this temperature for 2 h. At this stage, the Kirkendall effect began to play a role, which helped to promote the diffusion and mixing between different elements. This process helped to form a good structure of the alloy and promote the formation of pores. Then the temperature was continued to rise to 400 ℃, the heating rate was 5 ℃ / min, and the temperature was kept at this temperature for 30 min to remove the binder in the green body, and then the temperature was continued to rise to 900 ℃, the heating rate was 5 ℃ / min, and the temperature was kept for 2 h to promote the diffusion between the elements and the growth of the sintering neck to obtain a porous alloy material with uniform composition, good sintering neck and interconnected pore structure.
[0042] The high entropy alloying modified copper-tin alloy product of this example was prepared as a standard sample for mechanical property characterization. The characterization results are shown in the following table. Hardness (HV) Crushing strength Porosity 227 370 MPa 22.5%
[0043] Comparative Example 2 A method for preparing a high entropy alloyed modified copper-tin alloy is based on the preparation process of Example 2, except that: The final sintering temperature was changed from 900 °C to 700 °C.
[0044] The alloy product of this example was made into a standard sample for mechanical property characterization, and the characterization results are shown in the following table. Hardness (HV) Crushing strength Porosity 202 152 MPa 25.7%
[0045] The porous alloy material obtained by the above method has extremely poor mechanical strength. Incomplete sintering will reduce the mechanical strength of the material, and insufficient sintering between powder particles will make the material more likely to break when subjected to force. Due to insufficient sintering temperature, the diffusion degree between powder particles is insufficient, and sintering necks cannot be fully formed, which will cause the material density to fall short of the expected level, and the powder particles are not tightly bonded, resulting in a higher porosity in the finished product.
[0046] Comparative Example 3 A method for preparing a high entropy alloyed modified copper-tin alloy is based on the preparation process of Example 2, except that: The final sintering temperature was changed from 900 °C to 1100 °C, which is higher than the melting point of copper.
[0047] The alloy product of this example was made into a standard sample for mechanical property characterization, and the characterization results are shown in the following table. Hardness (HV) Crushing strength Porosity 215 431 MPa 15.7%
[0048] The porous alloy material prepared by the above method has significantly improved crushing strength compared with Example 1, but the porosity of the sample is significantly reduced, which indicates that the sintering neck of the sample is coarsened and the sintering is densified due to the overly high sintering temperature.
[0049] It can be clearly seen from Comparative Examples 2 and 3 that the technical solution of the present invention requires relatively strict control of the sintering process.
[0050] Example 3 A method for preparing a high entropy alloyed modified copper-tin alloy, which specifically comprises: (1) Powder preparation: CuMnNi alloy powder (purity>99.5 wt%, Cu 65 wt%, Mn15 wt%, Ni 20 wt%) with a particle size of 40-55 μm and SnZnPb alloy powder (particle size of about 60 μm, purity>99.5 wt%, Sn 55 wt%, Zn 35wt%, Pb 10 wt%) were taken, and 90% of the CuMnNi alloy powder and 10% of the SnZnPb alloy powder were mixed evenly by mass percentage, and the powders were mixed into a mixed powder in a nitrogen-protected V-type mixer. In order to obtain a uniform mixture, zirconium oxide balls were added to the original powder to improve the mixing efficiency. Each batch of powder was blended for 24 hours; (2) Granulation: Then, ethanol is used as a solvent and stearic acid accounting for 2.0 wt.% of the total mass of the mixed powder is mixed in a volume ratio of 1:1, and then the mixed powder is added to mix and granulation is performed to improve the compression molding effect of the sample; (3) Pressing: The mixed powder after granulation is dried and crushed again through a 100-mesh sieve, placed in a molding die, and pressed into a sheet (φ10 mm×2.0 mm) at a pressure of 200 MPa; (4) Sintering: When the vacuum degree is less than 1.0×10 -2Pa vacuum sintering furnace, the green body reaction synthesis was carried out by step sintering method, from room temperature to 150 ℃, the heating rate was 10 ℃ / min, and the temperature was kept at this temperature for 10 min to remove the gas molecules adsorbed by the green body, and then the temperature was continued to rise to 200 ℃, the heating rate was 2 ℃ / min, and the temperature was kept at this temperature for 2 h. At this stage, the Kirkendall effect began to play a role, which helped to promote the diffusion and mixing between different elements. This process helped to form a good structure of the alloy and promote the formation of pores. Then the temperature was continued to rise to 400 ℃, the heating rate was 5 ℃ / min, and the temperature was kept at this temperature for 30 min to remove the binder in the green body, and the temperature was continued to rise to 900 ℃, the heating rate was 5 ℃ / min, and the temperature was kept for 2 h to promote the diffusion between the elements and the growth of the sintering neck to obtain a porous alloy material with uniform composition, good sintering neck and interconnected pore structure, that is, high entropy alloying modified copper-tin alloy.
[0051] The alloy product of this example was made into a standard sample for mechanical property characterization, and the characterization results are shown in the following table. Hardness (HV) Crushing strength Porosity 232 368 MPa 22.3 %
[0052] From the characterization results in the above table, it can be seen that the high entropy alloyed modified copper-tin alloy prepared by the present invention has very excellent mechanical properties.
[0053] Example 4 A method for preparing a high entropy alloyed modified copper-tin alloy, which specifically comprises: (1) Powder preparation: CuMnNi alloy powder (purity>99.5 wt%, Cu 65 wt%, Mn15 wt%, Ni 20 wt%) with a particle size of 35-45 μm and SnZnPb alloy powder (particle size of about 45 μm, purity>99.5 wt%, Sn 55 wt%, Zn 35wt%, Pb 10 wt%) are taken, and 90% of the CuMnNi alloy powder and 10% of the SnZnPb alloy powder are mixed evenly according to the mass percentage. Here, finer powder is used to adjust the pore size to obtain a smaller average pore size. The powders are mixed in a nitrogen-protected V-type mixer to obtain a mixed powder. In order to obtain a uniform mixture, zirconium oxide balls are added to the original powder to improve the mixing efficiency. Each batch of powder is blended for 24 hours. (2) Granulation: Then, ethanol is used as a solvent and stearic acid accounting for 2.0 wt.% of the total mass of the mixed powder is mixed in a volume ratio of 1:1, and then the mixed powder is added to mix and granulation is performed to improve the compression molding effect of the sample; (3) Pressing: After drying the granulated mixed powder and re-crushing it through a 200-mesh sieve, the mixed powder is placed in a molding die and pressed into a sheet (φ10 mm×2.0 mm) at a pressure of 200 MPa; (4) Sintering: When the vacuum degree is less than 1.0×10 -2 In a vacuum sintering furnace at 10000 Pa, the reaction synthesis of the green body was carried out by step sintering method, from room temperature to 150 ℃, the heating rate was 10 ℃ / min, and the temperature was kept at this temperature for 10 min to remove the gas molecules adsorbed by the green body. Then the temperature was continued to rise to 200 ℃, the heating rate was 2 ℃ / min, and the temperature was kept at this temperature for 1 h. Due to the large specific surface area and more contact interfaces, the fine powder has a greater sintering driving force, and the sintering reaction usually occurs faster. Therefore, the fine powder may only need a shorter holding time during the sintering process, which is enough to achieve the required diffusion and material strength. At this stage, the Kirkendall effect begins to play a role, which helps to promote the diffusion and mixing between different elements. This process helps to form a good structure of the alloy and promotes the formation of pores. Then the temperature is continued to rise to 400 ℃ at a rate of 5 ℃ / min and kept at this temperature for 30 min to remove the binder in the green embryo, and then the temperature is continued to rise to 800 ℃ at a rate of 5 ℃ / min and kept at this temperature for 2 h to promote the diffusion between the elements and the growth of the sintering neck to obtain a porous alloy material with uniform composition, good sintering neck and interconnected pore structure, that is, high entropy alloying modified copper-tin alloy. Fine powder can achieve good diffusion and neck growth at a lower temperature, so a lower sintering temperature is usually required during the sintering process to avoid excessive growth, grain growth or abnormal phenomena during the sintering process.
[0054] The alloy product of this example was made into a standard sample for mechanical property characterization, and the characterization results are shown in the following table. Hardness (HV) Crushing strength Porosity 230 377 MPa 21.5%
[0055] From the characterization results in the above table, it can be seen that the high entropy alloyed modified copper-tin alloy prepared by the present invention has very excellent mechanical properties. In addition, the above mechanical property characterization results show that it can be very effectively used in the manufacture of oil-containing bearings.
Claims
1. A method for preparing a high entropy alloyed modified copper-tin alloy, characterized in that: The method comprises: 1) respectively taking copper alloy powder and tin alloy powder and mixing them evenly to obtain mixed powder; 2) The mixed powder is granulated and pressed to obtain a green body, and the green body is sintered in multiple stages to obtain a high entropy alloyed modified copper-tin alloy.
2. The method for preparing a high entropy alloyed modified copper-tin alloy according to claim 1, characterized in that: Step 1) the copper-containing alloy powder is composed of copper element and high melting point components; The melting point of the high melting point component is ≥1000°C; Step 1) the tin-containing alloy powder is composed of tin element and low melting point components; The melting point of the low melting point component is less than 1000°C.
3. The method for preparing a high entropy alloyed modified copper-tin alloy according to claim 1, characterized in that: Step 1) The copper-containing alloy powder is CuMnNi alloy powder, and its component percentage is: Cu 60~65 wt%, Mn 10~30%, the balance is Ni; Step 1) The tin-containing alloy powder is SnZnPb alloy powder, and its component percentage is: Sn 50~60 wt%, Zn 35~45 wt%, and the balance is Pb.
4. The method for preparing a high entropy alloyed modified copper-tin alloy according to claim 1, characterized in that: Step 1) The copper alloy powder accounts for 80-95% of the mixed powder by weight, and the remainder is tin alloy powder.
5. The method for preparing a high entropy alloyed modified copper-tin alloy according to claim 1 or 4, characterized in that: Step 1) The mixing is carried out by the following method: The copper-containing alloy powder and the tin-containing alloy powder are placed in a mixing bottle filled with protective gas, put into a mixer for mixing, and zirconium oxide balls are added as a mixing medium during the mixing process, and mixed for 24 to 48 hours.
6. The method for preparing a high entropy alloyed modified copper-tin alloy according to claim 1, characterized in that: Step 2) The granulation process is: Add the mixed powder to the ethanol solution containing the binder, mix and stir until it is dry, then crush and sieve to control the powder particle size to 100-300 mesh; The mass ratio of the binder to ethanol in the binder-containing ethanol solution is 1:(0.95-1.05), the amount of the binder is 2-3 wt% of the mixed powder, and the binder used is a binder soluble in ethanol.
7. The method for preparing a high entropy alloyed modified copper-tin alloy according to claim 1 or 6, characterized in that: Step 2) the pressing process controls the pressing pressure to be 50-250 MPa; Step 2) the multi-stage sintering is carried out under reducing gas and / or inert gas, or vacuum protection conditions; When the multi-stage sintering is carried out under vacuum protection, the vacuum degree is controlled to be 1.0×10 -2 ~1×10 0 Pa; Step 2) The multi-stage sintering includes low-temperature sintering and high-temperature sintering.
8. The method for preparing a high entropy alloyed modified copper-tin alloy according to claim 7, characterized in that: The low temperature sintering is a gradient heat treatment in the range of 120-420°C, which includes preheating at 120-150°C for 5-15 min, initial sintering at 180-220°C for 90-150 min, and debonding at 380-420°C for 25-35 min. The high temperature sintering is carried out at a temperature of ≥800°C and less than the melting point of the components contained in the copper alloy powder, and the sintering time is 1 to 3 hours.
9. A high entropy alloyed modified copper-tin alloy prepared by the method of any one of claims 1 to 8.
10. An application of the high entropy alloying modified copper-tin alloy as claimed in claim 9, characterized in that: The high entropy alloyed modified copper-tin alloy is used for manufacturing oil-containing bearings.